Physical characterization of frozen fruits from eight cultivars of the North American pawpaw (Asimina triloba) - Adainoo, Bezalel; Crowell, Brendan; Thomas, Andrew L.; Lin, Chung-Ho; Cai, Zhen; Byers, Patrick; Gold, Michael; Krishnaswamy, Kiruba (Frontiers in Nutrition, 2022)
Pawpaw (Asimina triloba [L.] Dunal) is an underutilized fruit native to North America. The fruit has a short shelf life, and browns and softens rapidly after harvesting. These characteristics present a challenge to the advancement of pawpaw as an economically viable specialty crop. This study evaluated the physical characteristics of eight cultivars of the pawpaw fruit and compared them to the physical properties of mango (Mangifera indica L.) fruits to establish the processing potential of pawpaw fruits. Fruits of the Susquehanna cultivar had the highest fruit weight and pulp yield, making them the most suitable for pulp processing. The pawpaw fruits had a pH higher than that of mangoes. Pawpaw fruits recorded lower juice contents compared to mangoes. Overleese fruits may be the best for pawpaw juice production. These findings can aid in the selection of processing equipment and guide processors in their efforts to utilize pawpaw fruits to avoid postharvest and post-processing losses.